Elderly residents in the community: gaining knowledge to support a rehabilitation nursing program - Ana da Conceição Alves Faria; Maria Manuela Ferreira Pereira da Silva Martins; Olga Maria Pimenta Lopes Ribeiro; Bárbara Pereira Gomes; Carla Sílvia Neves da Nova Fernandes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To analyze the socio-demographic and health conditions of the elderly living in the community and describe the pillars for the design of a rehabilitation nursing program in the community. Methods: Descriptive, cross-sectional study, with participation of 48 elderly selected by convenience sampling. Data collection took place between September 2018 and July 2019, in a health unit in northern Portugal, using a form. Results: All the elderly have pathological processes and overweight. Most of them are sedentary, have feelings of loneliness and inappropriate relational behaviors. In the last six months, 25% have fallen at least once, with notable changes in balance, lifestyles and perceived health status. Conclusion: The need for rehabilitation nurses to design and implement active aging programs that ensure individual accompaniment of the elderly by valuing lifestyles, balance training and promotion of social participation was highlighted.